Robust localization using geographic information in bistatic sonar - Kwang Hee Lee; Eui Cheol Jeong; Seongil Kim; Dong Seog Han (International Journal of Distributed Sensor Networks, 2017)
This article proposes a robust localization algorithm by improving the accuracy of the source position, receiver position, and sound speed using the known position of an object in the sea. The accuracy of those three types of information greatly influences the performance of the target localization in bistatic sonar. Although the locations of the source and receiver can be obtained using the global positioning system, there are still some position errors due to the limitations of global positioning system–based positioning systems and tidal current. In addition, the speed of the sound in the sea changes with temperature. The target estimation error was analyzed mathematically in terms of the mentioned errors. An improved localization is proposed using the accurate positions of objects in the sea, which can compensate for the errors in the source position, receiver position, and sound speed. The proposed algorithm is compared with the conventional algorithm through computer simulations.